2007
DOI: 10.1007/s11056-007-9067-2
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variation and recent evolutionary history of eastern hemlock (Tsuga canadensis) in the southeastern United States

Abstract: Eastern hemlock (Tsuga canadensis [L.] Carr.) is a widespread and ecologically important conifer species of eastern North America that is threatened by the hemlock woolly adelgid (Adelges tsugae Annand), a pest introduced into the United States from Asia in the 1920s. Information about the genetic composition of eastern hemlock is necessary to guide ex situ conservation efforts in the southeastern United States, where the species is expected to harbor relatively high amounts of genetic variation in areas of Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…An analysis of highly conserved chloroplast DNA polymorphisms primarily among disjunct populations identified little differentiation (Wang et al 1997), while Zabinski (1992) detected little allozyme variation within eastern hemlock in a study that was focused in the Midwestern portion of the eastern hemlock range. In a study that sampled 20 populations from the Southeastern portion of the range, Potter et al (2008) also found low allozyme diversity in hemlock but reasonably high population differentiation. A range-wide analysis using seven haploid chloroplast DNA loci (Lemieux et al 2011) also detected low among-population differentiation and, consistent with Potter et al (2008), greater differentiation and relatively high allelic richness among southeastern Appalachian populations.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…An analysis of highly conserved chloroplast DNA polymorphisms primarily among disjunct populations identified little differentiation (Wang et al 1997), while Zabinski (1992) detected little allozyme variation within eastern hemlock in a study that was focused in the Midwestern portion of the eastern hemlock range. In a study that sampled 20 populations from the Southeastern portion of the range, Potter et al (2008) also found low allozyme diversity in hemlock but reasonably high population differentiation. A range-wide analysis using seven haploid chloroplast DNA loci (Lemieux et al 2011) also detected low among-population differentiation and, consistent with Potter et al (2008), greater differentiation and relatively high allelic richness among southeastern Appalachian populations.…”
Section: Introductionmentioning
confidence: 95%
“…In a study that sampled 20 populations from the Southeastern portion of the range, Potter et al (2008) also found low allozyme diversity in hemlock but reasonably high population differentiation. A range-wide analysis using seven haploid chloroplast DNA loci (Lemieux et al 2011) also detected low among-population differentiation and, consistent with Potter et al (2008), greater differentiation and relatively high allelic richness among southeastern Appalachian populations. These results led both sets of authors to conclude that the majority of eastern hemlock genetic diversity may have originated from a Pleistocene glacial refuge in this region.…”
Section: Introductionmentioning
confidence: 95%
“…Despite its restricted occurrence, our results indicate that Carolina hemlock exhibits a moderate amount of genetic variation (Camcore, 2006). At the same time, eastern hemlock, which is found throughout eastern North America, appears to have relatively low genetic variation in the southeastern states (Potter et al, 2008).…”
Section: Evolution and Genetic Diversitymentioning
confidence: 99%
“…Low genetic diversity in eastern hemlock (Potter et al 2008(Potter et al , 2012 and Carolina hemlock (Campbell 2014), coupled with generally high levels of inbreeding across both species, highlight the need for quick and decisive action to assess the genetic diversity of previously undersampled areas and to fully protect the genetic composition of each species.…”
Section: Genetic Diversity Implications and Future Effortsmentioning
confidence: 99%